2016
DOI: 10.1002/pc.24183
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic analysis of functionally graded cylinders reinforced by wavy CNT using a mesh‐free method

Abstract: FIG. 6. (a) Hoop stress, (b) radial stress, (c) radial displacement, and (d) temperature along radial direction for third model of infinite length CNTRC cylinders. [Color figure can be viewed at wileyonlinelibrary.com]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Moradi‐Dastjerdi et al investigated the thermo‐elastic behavior of poly(methyl methacrylate) (PMMA) reinforced with functionally graded carbon nanotubes (FG‐CNT) under thermal and mechanical loadings in an analytical way and using mesh‐free technique. They showed that fillers led to the improvement of thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moradi‐Dastjerdi et al investigated the thermo‐elastic behavior of poly(methyl methacrylate) (PMMA) reinforced with functionally graded carbon nanotubes (FG‐CNT) under thermal and mechanical loadings in an analytical way and using mesh‐free technique. They showed that fillers led to the improvement of thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the individual volume fractions of the matrix contained in the face sheets of the sandwich panel can be obtained using the following mathematical relation: along the corresponding material axes are evaluated using the common rule of mixture [47,48]: 12 12 (1 )…”
Section: Cnt Gradations and Elastic Propertiesmentioning
confidence: 99%
“…Shokri-Oojghaz [24] stud-ied the effect of reinforcing with aggregated CNT on the stress distributions of nanocomposite sandwich cylinders based on finite element method. Temperature effect on the static and dynamic responses of nanocomposite cylinders reinforced with wavy CNT were studied by Moradi-Dastjerdi et al [25][26][27]. Safaei et al [28] analyzed the free vibration of nanocomposite plates with CNTs embedded in amorphous polyethylene.…”
Section: Introductionmentioning
confidence: 99%